2020
DOI: 10.3389/fnmol.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

Sarcosine Suppresses Epileptogenesis in Rats With Effects on Hippocampal DNA Methylation

Abstract: Epileptogenesis is a common consequence of brain insults, however, the prevention or delay of the epileptogenic process remains an important unmet medical challenge. Overexpression of glycine transporter 1 (GlyT1) is proposed as a pathological hallmark in the hippocampus of patients with temporal lobe epilepsy (TLE), and we previously demonstrated in rodent epilepsy models that augmentation of glycine suppressed chronic seizures and altered acute seizure thresholds. In the present study we evaluated the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…1A ). The intracellular level of these amino acids was varied by increasing their concentration in the medium or by reducing their uptake by employing 4-Fluorophenyl-L-glycine (4LFPG) and sarcosine (SARC), which inhibit serine and glycine importers SLC1A4/SLC1A5 and GlyT1, respectively 15 , 16 . Using these inhibitors, we observed a reduction of the intracellular content of serine and glycine of about 18% for 4LFPG and 40% for SARC (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A ). The intracellular level of these amino acids was varied by increasing their concentration in the medium or by reducing their uptake by employing 4-Fluorophenyl-L-glycine (4LFPG) and sarcosine (SARC), which inhibit serine and glycine importers SLC1A4/SLC1A5 and GlyT1, respectively 15 , 16 . Using these inhibitors, we observed a reduction of the intracellular content of serine and glycine of about 18% for 4LFPG and 40% for SARC (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The higher level of the presumed sarcosine signal observed for LCRC (compared with that noted for RCRC) warrants further investigation. Sarcosine has recently been implicated in the methylation of genes associated with several diseases, including CRC [37][38][39]. In one study, the incubation of prostate cells with sarcosine stimulated DNA methyltransferases (DNMTs), resulting in increases in global DNA methylation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, the authors suggested that by acting in the demethylation pathway, sarcosine could attenuate the progression of epilepsy. 150 DNMTs also play a crucial role in DNA methylation, and changes in these enzymes have been observed in tissue from patients with MTLE. [151][152][153] However, to our knowledge, there is no published study in which the authors aimed to investigate the pharmacologic response of the DNMT inhibitors and their possible relationship to pharmacoresistance in patients with MTLE.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Moreover, TET1 expression was upregulated. Based on these results, the authors suggested that by acting in the demethylation pathway, sarcosine could attenuate the progression of epilepsy 150 …”
Section: Epigenomicsmentioning
confidence: 99%
See 1 more Smart Citation